Lasers Congress 2016 (ASSL, LSC, LAC) 2016
DOI: 10.1364/assl.2016.ath1a.3
|View full text |Cite
|
Sign up to set email alerts
|

Watt-level Nanosecond 589 nm Source by SHG of a Cascaded Raman Amplifier

Abstract: We present a power-scalable nanosecond source operating at 589 nm by frequency-doubling a cascaded Raman amplifier that is pulse-pumped by an ytterbium-fiber master oscillator power amplifier system and seeded with a narrow linewidth CW signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In recent years, our group has demonstrated such sources at 1.12 µm, 1.18 µm and 1.24 µm, which were all then subsequently frequency doubled for biophotonics imaging applications. [27][28][29][30][31] However, as we demonstrate in this work, NIR Raman fiber systems are also highly suitable for upconversion to the MIR.…”
Section: Stimulated Raman Scattering In Optical Fibersmentioning
confidence: 85%
“…In recent years, our group has demonstrated such sources at 1.12 µm, 1.18 µm and 1.24 µm, which were all then subsequently frequency doubled for biophotonics imaging applications. [27][28][29][30][31] However, as we demonstrate in this work, NIR Raman fiber systems are also highly suitable for upconversion to the MIR.…”
Section: Stimulated Raman Scattering In Optical Fibersmentioning
confidence: 85%
“…The main drawback of synchronously pumped Raman lasers is that the pump repetition rate needs to be precisely tuned to the Raman cavity length, thereby precluding repetition rate adjustment and pulse-duration tunability. To overcome this limitation, in our recent works we used narrow linewidth continuous-wave (CW) signals to seed Raman amplifiers that were pulse-pumped using Yb:fiber MOPA systems [30]- [32].…”
Section: Seeded Raman Amplificationmentioning
confidence: 99%
“…In [32], we extended the CW seeded, pulsed-pumped Raman amplifier concept to the second Stokes shift at 1179 nm by using a cascaded Raman amplifier architecture. The 1120 nm output of a CW-seeded Raman amplifier (pulse-pumped by a Yb:fiber MOPA system) was used to pulse-pump a second Raman amplifier stage that was seeded by a CW signal at 1179 nm from a DFB laser diode.…”
Section: Seeded Raman Amplificationmentioning
confidence: 99%
“…In our previous works, we have shown that Raman amplifiers pulse-pumped by Yb:fiber master oscillator power amplifier (MOPA) systems, seeded with narrow linewidth CW signals, followed by frequency-doubling in periodically poled crystals are an effective route to generating yellow-green pulses [3][4][5]. The use of a discreet Raman amplifier, however, has an impact on the power-scaling potential due to the insertion loss of the components and deleterious nonlinear effects in the Raman amplifier fiber.…”
Section: Introductionmentioning
confidence: 99%